Christian Education in Respecting Catholic Marriage: A Case Study of Young Families in Divine Mercy Parish, Biak - Selitubun, Marthinus (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
In contemporary society, young families often face challenges in understanding and implementing the teachings of the Catholic Church on marriage. In practice, there are still young couples who do not fully appreciate the meaning of loyalty, openness to life, and shared responsibility in family life. This indicates a gap between the teachings of Christian Education regarding the sacredness and steadfastness of Catholic marriage bonds and the reality of family life lived by the congregation. This study aims to identify the impact of Christian education on the understanding and experience of Catholic marriage among young families in the Divine Mercy Parish, Biak City. This study uses a quantitative approach, this study utilizes Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to examine the relationship between Christian education (X1), understanding of Catholic marriage (X2), experience of Catholic marriage (Z), and a deeper understanding of Catholic marriage (Y). Data were collected through questionnaires from 300 young family members, and PLS analysis was used to test the hypothesis. The results showed a significant positive influence of Christian education on knowledge and experience of marriage, which confirms its role in deepening insight into Catholic marriage. Recommendations for improving Christian education in the parish are also provided. The implications of this study indicate the importance of strengthening Christian Education, especially in premarital guidance and pastoral care for young families in the Divine Mercy Parish, Biak. The results of the study can be a basis for church leaders and faith educators in designing more contextual guidance programs, touching the reality of people's lives, and relevant to the challenges of today's young families.